The Effect of Perceived Usefulness, Perceived Ease of Use, Perceived Trust, and Perceived Risk on MSMEs' Interest in Using the Quick Response Code Indonesian Standard (QRIS) as Payment Method - Rona Tumiur Mauli Carolin Simorangkir (Green Publisher, 2025)
This study aims to investigate and analyze the impact of perceived usefulness, perceived ease, perceived trust, and perceived risk on the interest of SMEs in Tangerang in using the QRIS payment method. The subjects of the study are SME owners in the area. The analysis method employed is causal study with a quantitative approach, based on the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). Primary data were collected through questionnaires and analyzed using Partial Least Squares (PLS) software with a Structural Equation Modeling (SEM) approach. The results indicate that perceived usefulness, perceived ease, perceived trust, and perceived risk significantly influence SMEs' interest in using QRIS.